Workplace physical aggressions in Italy and Emilia Romagna region - Zanardi, Francesca; Broccoli, Marco; Falasca, Giovanni; Toderi, Stefano (La Medicina del Lavoro, 2021)
Background: Workplace physical aggressions determine severe consequences for people and organizations. Previous studies reported their spread in organizations and described factors related to their occurrence (e.g. aggressor within/outside the organization, type of activity, etc.). However, such data are not available in the Italian work contexts, limiting the possibility of intervention. Objectives: This study aims to provide a description of workplace physical aggressions in the Italian context and the Emilia-Romagna region, considering the main variables described in the literature. Methods: We used data available from the "Flussi informativi" database, containing national data provided by INAIL (National Institute for Insurance against Accidents at Work), which concern all injuries, occupational illness and insured companies’ information, from 2000 to 2018. Information about aggressions in the workplace in Italy and Emilia-Romagna are derived from a subset of these data, coded according to ESAW (European Statistics for Accidents at Work) requirements. The number of events per year per 100,000 estimated insured employees by INAIL is considered as an indicator. Results: In the period 2014-2018, 23,084 injures from aggression were registered in Italy (an average of 28.7 events per 100,000 employees) and 2,308 in Emilia Romagna (30.2). Aggressions by people outside the organization accounted for 85.14 % in Italy and 87.87% in Emilia-Romagna region. “Health and social services”, “Offices and other activities” and “Transportation” were the sectors that showed the highest numbers of events and rates. Furthermore, we reported detailed results about the variation of the events between professions, the site and nature of the lesion and gravity of events. Discussion: The study provides a description of workplace physical aggressions in the Italian context and we discuss the implication of these results for primary, secondary and tertiary prevention strategies of intervention.